Beyond Masculinity: Gender, Conflict and Post-Conflict Reconstruction in Northern Uganda - Esuruku, R. S. (African Journals Online (AJOL), 2013)
Masculinity and femininity debates of armed conflict in Africa have always regarded men as fighters and women as passive victims of war. The exclusion of women from the armed forces in most traditional societies originated from the assumption that women are a weaker sex and therefore cannot manage military life. Nevertheless, women in Uganda have voluntarily joined the armed forces, while some of them have been abducted and forcefully recruited into the rebel forces. Notwithstanding the central role women have played in the armed conflict in Northern Uganda, they have been side-lined in the processes of peace negotiation and post conflict reconstruction of the region. This paper looks at how masculinity is manipulated in conflict and the role women have played in the conflict, peace process and post conflict reconstruction in Northern Uganda. Keywords · Gender · Post-conflict reconstruction · Transitional justice